Likeable badass eaudiobook How women get the success they deserve. - Fragale, Alison (Books on Tape, 2024)
Behavioral scientist Alison Fragale offers powerful new insights and a practical playbook for women to advance in any workplace, full of tips, tricks, and strategies to help secure that elusive corner office. Over decades of research, speaking engagements, and mentorship, psychologist and professor Alison Fragale encountered recurring questions from high powered and early career women alike: How do women thread the needle of kindness and competence in the workplace? How can women earn credit for their accomplishments, negotiate better, and navigate complex office politics without losing the goodwill of their peers? Fragale investigated and determined that many women's workplace issues boil down to what psychologists call status: the perception of them by others. No amount of power— no degree, title, or paycheck— will raise a woman's workplace stature unless it also affects how others see her. Acknowledging this roadblock, Fragale pulls back the curtain on how we can change how others see us by developing our standing as a "likeable badass." By cultivating perceptions of warmth and assertiveness, women can achieve the kind of reputation that leads to a seat at the table and a fulfilling career path. Likeable Badass is equal parts behavioral science and life hacks, weaving together rigorous research with actionable advice and impactful stories from a diverse array of women. This is a warm, heartening book written for women, their allies, and anyone who struggles to rise, and wants evidence-based, practical strategies for success, served with a side of inspiration and humor.